Validity and Reliability of the Turkish Version of the COVID Stress Scale - BAYRI BİNGÖL, FADİME; DEMİRGÖZ BAL, MELTEM (KOREAN SOC NURSING SCIENCE, 2021)
Purpose: The aim of this study was to assess the Turkish adaptation of the COVID Stress Scale (CSS) on the basis of determining the stress caused by the coronavirus disease (COVID-19) pandemic, and to test its validity and reliability. Methods: The English CSS was translated into Turkish using forward and backward translation. Data were collected online from 360 participants. Construct validity was evaluated using confirmatory factor analysis, exploratory factor analysis, and content validity. Pearson product-moment correlation, Cronbach's alpha reliability coefficient, and test-retest methods were used to evaluate reliability. Results: The Turkish version of the CSS has 36 items consistent with the original scale and has five factors: COVID danger and contamination, socioeconomic consequences of COVID, COVID xenophobia, traumatic stress due to COVID, and compulsive checking for COVID. The construct validity of the Turkish version of the CSS was verified by the adjusted goodness of fit index >.85, and comparative fit index > .95. The content validity index of each item was 91%. The corrected item-total correlations of the scale ranged from .51 to .89. Internal consistency was reliable, with a Cronbach's alpha of .93. Conclusion: The Turkish version of the CSS is valid and reliable. It can be used as a measurement tool for the assessment of COVID-related stress.
Keywords: Reliability and Validity; Factor Analysis; COVID-19; COVID-19 Stress Syndrome